Thin Films of Highly Planar Semiconductor Polymers Exhibiting Band-like Transport at Room Temperature - Lee, Jiyoul; Chung, Jong Won; Kim, Do Hwan; Lee, Bang-Lin; Park, Ieong-Il; Lee, Sangyoon; Haeusermann, Roger; Batlogg, Bertram; Lee, Sang-Soo; Choi, Insil; Kim, Il Won; Kang, Moon Sung (AMER CHEMICAL SOC, 2015)
We report the observation of band-like transport from printed polymer thin films at room temperature. This was achieved from donor-acceptor type thiophene-thiazole copolymer that was carefully designed to enhance the planarity of the backbone and the resulting transfer integral between the macromolecules. Due to the strong molecular interaction, the printed polymer film exhibited extremely low trap density comparable to that of molecular single crystals. Moreover, the energy barrier height for charge transport could be readily reduced with the aid of electric field, which led formation of extended electron states for band-like charge transport at room temperature.
Keywords: DENSITY-OF-STATES; HIGH-MOBILITY; HOLE MOBILITY; SIDE-CHAIN; FIELD; THIOPHENE; CRYSTALLINITY; COPOLYMERS; DEPENDENCE